Bibliometric Analysis of Palm Oil Competitiveness Study in Indonesia and The Linkage to Agricultural Trade - Bahtera, Novyandra Ilham; Novianti, Tanti; Septiyanti, Ratih (Universitas Negeri Gorontalo, 2025)
The global palm oil industry has become a focal point in agricultural trade due to its economic significance and environmental implications. As one of the world’s largest producers, Indonesia faces increasing pressure to maintain its competitiveness while addressing sustainability and trade policy challenges. This study aims to assess the development of scientific literature on Indonesian palm oil competitiveness and its relationship with global agricultural trade dynamics. The study was conducted using bibliometric analysis of 648 scientific articles obtained from Google Scholar and Scopus using the keyword